Involvement of PI3K/Akt signaling pathway in promoting osteogenesis on titanium implant surfaces modified with novel non-thermal atmospheric plasma - Zheng, Zheng; He, Yanjin; Long, Li; Gan, Shuaiqi; Chen, Shujiang; Zhang, Min; Xu, Jia; Fu, Ruijie; Liao, Yihan; Zhu, Zhimin; Wang, Hang; Chen, Wenchuan (Frontiers in Bioengineering and Biotechnology, 2022)
Non-thermal atmospheric plasma (NTAP) modification to induce a hydrophilic titanium (Ti) surface with less carbon contamination, has been demonstrated to boost the osteogenic responses. In this study, we investigated the underlying bone formation mechanism of NTAP-Ti, and the involvement of PI3K/Akt signaling pathway in regulating osteogenic activities on NTAP-Ti surfaces. NTAP was employed for Ti activation, and PI3K inhibitor, LY294002, was applied to the suppression of PI3K/Akt pathway. We systematically and quantitatively detected the cell morphology, attachment, proliferation, osteogenic differentiation and mineralization of MC3T3-E1 mouse preosteoblasts, and molecular expressions involved in osteogenesis and PI3K/Akt signaling pathway in vivo and in vitro. A descent in osteoblast proliferation on Ti surfaces in relation to LY294002. Alkaline phosphatase (ALP) activity, as well as matrix mineralization, was mitigated by PI3K inhibitor in NTAP-Ti. Likewise, the expression levels of osteogenesis-related genes (ALP, osteocalcin (Ocn), osteopontin (Opn) and runt-related transcription factor 2 (Runx2)) on NTAP-Ti were notably attenuated by LY294002, as confirmed by the results of osteogenesis-related proteins (ALP, and Runx2) expression analysis. In addition, the expression of PI3K/Akt signal pathway proteins further verified the inhibition of LY294002 on Ti surfaces modified by NTAP. Collectively, the PI3K/Akt signal pathway was involved in the amelioration of osteogenesis induced by NTAP modification. NTAP treatment for Ti activation is promising in augmented osteogenic potential through the activation of PI3K/Akt signal pathway.